The influence of credibility and social capital on e-wom with attitude as a mediation variable by Gen Z Tiktok users in Padang City - Fitria Asri; Vidyarini Dwita (Universitas Negeri Padang, 2021)
This study aims to analyze how the influence of credibility and social capital on EWOM with attitude as a mediation variable by gen Z TikTok users in Padang City (study on brand Somethinc). This research was conducted using quantitative methods. The population of this research is gen Z TikTok users in Padang City who ever sees or reviews about brand Somethinc. The research sample was 200 respondents. This study uses a structural equation model (SEM) test with smart-PLS 3.0 software. The results of this study include: (1) Credibility has a positive significant effect on Attitude. (2) Social Capital has a positive significant effect on Attitude. (3) Attitude has a positive significant effect on EWOM. (4) Social Capital has a positive significant effect on Credibility. (5) Credibility has a significant indirect effect on EWOM with Attitude as a mediating variable. (6) Social Capital has a significant indirect effect on EWOM with Attitude as a mediating variable.